DEF6 aggregation is linked to active translation and mRNA turnover in T cells - Remon, Kerry (2017)
Spatiotemporal responses to extracellular signals have been documented in a wide variety of cells, such as neuronal synapses, cytotoxic T lymphocytes, germ cells and during embryo development. Selective release of a key molecule allows a cell to respond at a given moment, and cells ensure that the response can be initiated instantly by pre-producing and packaging the molecule, often storing the molecule as a granule. Differentially Expressed in FDCP6 is a guanine nucleotide exchange factor, primarily expressed in T cells, which has been previously shown to form cytoplasmic aggregates when phosphorylated by ITK. DEF6 also translocates to the immunological synapse following phosphorylation by LCK in response to antigenic presentation. As a result, DEF6 is a likely candidate in mediating a spatiotemporal response to an extracellular signal in T cells. Data presented in this work suggest that endogenous DEF6 forms cytoplasmic granules in a variety of T cell states and the DEF6 mutant Y210EY222E, which mimics ITK phosphorylation, interacts with mRNA. Moreover, DEF6 is hypothesised to have two unconventional RNA binding domains; a feature which has also been described in the literature within proteins that catalyse glycolysis. DEF6 is also shown to be in close proximity to PABP and eIF4E, both of which are translation factors, as well as active translation in resting Jurkat T cells and the immunological synapse. Furthermore, endogenous DEF6 co-localises with 4E-T, a P-body marker which is involved with miRNA mediated decay, in resting and stressed Jurkat T cells. These data corroborate that of Hey et al. (2012) and suggests that DEF6 does indeed interact with P-bodies. Finally, translocation of DEF6 appears to occur in response to an extracellular signal alternative to the T cell receptor during T-T communication and that the translocation may occur in vesicle-like structures in close proximity to LFA-1. Consequently, these data identify a novel link between DEF6 and active translation as well as mRNA turnover and that the extracellular signal required for this spatial response is not antigen presenting cell specific but rather a response to LFA-1 stimulation.